IMPLEMENTASI MEDIA VISUAL DALAM PEMBELAJARAN IPAS SISTEM PEREDARAH DARAH KELAS V MI AL-BAROKAH AJUNG JEMBER - Nur Hidayah; Ayu Nizahiroh; Riska Yulianti; Muhammad Swignyo Prayogo (CV. Adiba Aisha Amira, 2025)
This study aims to describe the application of visual media in teaching Natural and Social Sciences (IPAS) on the topic of the human circulatory system in grade V at MI Al-Barokah Ajung Jember. The background of this study stems from the low interest and understanding of students regarding the concept of the human circulatory system, which is caused by teaching methods that are still traditional and teacher-centered. This study uses a qualitative approach with a descriptive research type. The research subjects include teachers and fifth-grade students at MI Al-Barokah Ajung Jember. Data were collected through observation, interviews, and documentation. The results of the study show that the use of visual media, such as anatomical drawings and posters illustrating the circulatory system, can increase students' motivation to learn and their understanding of the material being taught. In addition, learning becomes more interesting, interactive, and enjoyable. Thus, the use of visual media has been proven to have a positive effect on improving the quality of science education, particularly in the subject of the human circulatory system in fifth grade at MI Al-Barokah Ajung Jember.